Environmental impacts assessment of biodiesel production from Jatropha and WCO - Khang, Dinh Sy; Hung, Duong Phuoc; Tuan, Phan Dinh (Vietnam Journal of Science and Technology, 2019)
Biodiesel that is produced from renewable resources has been rising as a promising candidate to replace conventional energy. Vietnam, with a large amount of land used in agriculture or forestry, has advantaged conditions to produce and develop renewable energy from biomass resources. However, developing biodiesel from agricultural product may affect food security significantly. Therefore, Jatropha that is inedible and waste cooking oil (WCO) could be suitable to biodiesel production. One of the most important aims of using biodiesel to replace fossil diesel is to reduce environmental impacts, particularly impact on Climate Change. It is necessary to analyze the environmental performance of biodiesel through the entire life cycle. In this paper, life cycle assessment of biodiesel production and use was applied to measure the environmental performance of biodiesel produced from jatropha oil and WCO under Vietnam conditions. Some main emissions, such as CO2, NOx, PM, CH4, VOC and land use, were computed through a cradle-to-grave analysis. The result shows that when using Jatropha biodiesel to replace diesel, global warming potential (GWP) and photochemical oxidant formation potential (POFP) could be improved, but some other impacts, such as acidification potential (AP) and eutrophication potential (EP), could tend to increase. The environmental impacts of WCO biodiesel are all reduced in comparison with fossil diesel.